OPTIMALISASI PERAN KADER PMO (PENGAWASAN MENELAN OBAT) DALAM KEPATUHAN MINUM OBAT PADA PENDERITA TUBERKULOSIS PARU - Hanafi, Wibowo; Wospakrik, Frengki; Iyai, Melkias; Srianingsih, Srianingsih (Jurnal LENTERA, 2025)
Tuberculosis (TB) can be addressed through the implementation of an effective treatment regimen. Non-compliance with Tuberculosis treatment can lead to drug resistance and increase the risk of death. This community service activity aims to improve medication adherence in Pulmonary Tuberculosis patients by optimizing the role of Medication Supervisor Cadres (PMO) in Karang Tumaritis Village, Nabire Regency, Central Papua. The methods used in this activity include socialization, training, and mentoring for PMO Cadres by involving them as supervisors to ensure patient adherence to the tuberculosis treatment regimen.Training was provided to increase the cadres’ knowledge of their duties, measured through pretests and post-tests. The results showed a significant increase in knowledge, with an average pretest score of 58.9% and post-test scores reaching 85-90%. In addition, regular monitoring conducted by the cadres improved patient adherence, reduced the risk of transmission, and supported treatment success. This activity concluded that optimizing the role of PMO Cadres is effective in improving medication adherence in Tuberculosis patients and can serve as a model to be implemented in other areas to combat Tuberculosis.